2016
DOI: 10.20344/amp.6058
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Consensus on the Diagnosis, Prevention and Treatment of Anaemia in Inflammatory Bowel Disease

Abstract: <p><strong>Introduction:</strong> Anaemia can be considered the most common extra-intestinal manifestation in inflammatory bowel disease. Nevertheless, anaemia is often under-diagnosed and under-treated both in adults and children with inflammatory bowel disease. Herein, we report the consensus statements on the management of anaemia in inflammatory bowel disease developed by the Portuguese Working Group on Inflammatory Bowel Disease (known as Grupo de Estudo da Doença Inflamatória Intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 104 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…It has been suggested that anti-TNF therapy regulates erythropoiesis at various levels. However, some studies have shown that the prevalence of anemia was higher in patients treated with anti-TNF agents than those treated with other drugs ( e.g ., immunomodulators, corticosteroids, aminosalicylates)[ 48 ]. The higher prevalence reported in those studies is associated with the fact that these drugs (anti-TNF agents) are often used in patients with increased disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that anti-TNF therapy regulates erythropoiesis at various levels. However, some studies have shown that the prevalence of anemia was higher in patients treated with anti-TNF agents than those treated with other drugs ( e.g ., immunomodulators, corticosteroids, aminosalicylates)[ 48 ]. The higher prevalence reported in those studies is associated with the fact that these drugs (anti-TNF agents) are often used in patients with increased disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…86 yet guidelines often lack agreement on test cut-off values for these parameters. 4 Serum ferritin levels are TABLE 1 Iron deficiency anemia has more guideline coverage than iron deficiency: summary of iron deficiency diagnostic measures, independent of anemia [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] Recommended iron deficiency threshold values independent of anemia although a CRP level of 5 mg L 21 is the most common threshold, 64 this is not recognized in most guidelines 68…”
Section: Diagnosis Of Iron Deficiency In Chronic Inflammatory Condimentioning
confidence: 99%
“…Iron deficiency anemia has more guideline coverage than iron deficiency: summary of iron deficiency diagnostic measures, independent of anemia[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] …”
mentioning
confidence: 99%
“…The latest Portuguese [38] and European (ECCO) [39] consensus statements on the management of ID and anemia in IBD do not specifically address the pediatric population. However, ID is the most common nutritional deficit and IDA the most frequent form of anemia in this age group, and hence the opportunity to assess and monitor children's iron reserves and to investigate ID and IDA diagnosis in this age group should always be assured.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this consensus, elaborated by the Portuguese Society of Pediatric Gastroenterology and Nutrition (SPGNP) -Anemia-IBD Working Group, is to propose recommendations for the management of anemia in pediatric patients with IBD, based on ECCO [39] and on the Portuguese [38] consensus on anemia in IBD, specifically focusing on the features of ID and IDA in pediatric age.…”
Section: Introductionmentioning
confidence: 99%